Methane hydrate dissociation in the presence of novel benign additives - Gaurav Bhattacharjee; Vivek Barmecha; Nilesh Choudhary; Nawal K. Pande; Parivesh Chugh; Rajnish Kumar (Energy Procedia, 2019)
The apparent drawbacks of the classical approaches towards dissociation of natural gas hydrates have resulted in a paradigm shift into the development of new hybrid hydrate dissociation practices combining the various basic hydrate dissociation techniques. Another approach that can be followed to maximize the efficiency of gas production from natural gas hydrate reserves is the identification of benign additives which when used even in sparingly small concentrations may enhance the kinetics of hydrate dissociation. In the present work, a class of such additives, never reported before, have been unveiled and christened as Low Dosage Hydrate Dissociation Promoters (LHDPs). The additives were first short listed from a wide potential pool using a lab scale ( 250 ml) stirred tank reactor setup and then further studied using a bench scale ( 2.35 l) reactor setup where they were injected in the form of a water-additive stream to dissociate hydrates. The dissociation approach followed in the case of the bench scale reactor experiments was a combination of the thermal stimulation and depressurization processes along with the element of injection of additives. For both sets of experiments (lab and bench scale), the newly identified LHDPs were found to enhance the kinetics of methane hydrate dissociation as compared to pure water. It was observed that concentration of additive and its flow rate also affect the kinetics of methane hydrate dissociation. An energy and efficiency analysis for the hydrate dissociation method in the case of bench scale rector revealed that additive presence enhanced the energy ratio and thermal efficiency four fold as compared to pure water.
Keywords: Depressurization; Dissociation; Energy Ratio; kinetics; LHDP; methane hydrate; Thermal Efficiency; thermal stimulation